From lab to life: technological innovations in transforming cancer metastasis detection and therapy - Soumya Basu; Satish Sasikumar; Subhayan Sur; Viniti Vaidya; Supriya Kheur; Samir Gupta; Amit Ranjan; Manash Paul; Neelu Nawani; Aditi Bhat; Nikita Adak (Discover Oncology)
Abstract Cancer metastasis remains the leading cause of cancer-related mortality and represents a major therapeutic bottleneck, primarily due to the limited availability of effective, targeted treatment strategies. While key oncogenic drivers such as HER2, EGFR, PIK3CA, KRAS, and BRAF activate critical pathways like PI3K/AKT and MAPK/ERK, promoting tumor proliferation and migration and metastasis. In addition, metastasis is also influenced by environmental factors, microbiomes, and genomic alterations. This complex interplay underscores the urgent need for comprehensive mechanistic insights into metastatic progression, alongside the development of innovative translational platforms. This review explores the external contributors to metastasis, including air and water pollution, chemical exposures, and microbiome dysbiosis, which impact tumor progression and immune evasion. It also discusses the roles of viral infections, organotropism, and genomic regulation in driving metastasis heterogeneity. To address these challenges, a novel integrative framework has been proposed that connects environmental modulators, tumor-associated microbiota, and oncogenic genomic alterations with cutting-edge methodologies such as 3D bioprinting, microphysiological systems, liquid biopsy, and advanced in vitro and in vivo models. High-resolution imaging and AI-driven multi-omics integration further enhance the precision of these approaches. By transcending traditional and reductionist, tumor-centric paradigms, this framework advocates for a systems-level, translational framework that bridges molecular insights with clinical applicability. Ultimately, this strategy seeks to resolve persistent therapeutic challenges in metastatic cancer management through interdisciplinary collaboration.